PERBEDAAN PELAKSANAAN PROGRAM SICENTIK (SISWA CARI JENTIK) DI SDN PEDALANGAN 1 DAN SDN PEDALANGAN 2 KECAMATAN BANYUMANIK - Rahmasari, Annisya Aulia; Jati, Sutopo Patria; Nandini, Nurhasmadiar (Jurnal Manajemen Kesehatan Indonesia, 2024)
Padangsari Community Health Center is one of the community health centers in Banyumanik sub-district with a low percentage of SICENTIK's participation. This research aimed to conduct implementation observation research at SDN Pedalangan 1 and SDN Pedalangan 2. This research was a qualitative descriptive research that uses purposive techniques in selecting informants. It was held on November 2023 - April 2024. Data collection using in-depth interviews and literature study. The results of this research show that there are several differences in implementation between SDN Pedalangan 1 and SDN Pedalangan 2 shown by the place of this program was implemented, principal's role, division of labour, form letter, knowledge and experience of implementer, shared commitments, implementer's preparations, and evaluations of the program.  The study's findings demonstrate that the lack of Standard Operating Procedures (SOP), success indicators, and health center controls is the primary cause of the disparities between the two schools. Thus, in addition to creating disparities between the two institutions, it also results in wasteful and poor program execution. Then, during the program's implementation, it was found that the community health center and SDN Pedalangan 2's supervisor had acted in an unprofessional manner, which had led to a lackluster implementation of SICENTIK in schools and community health centers.